System structure and control : preprints of the IFAC workshop, Prague, Czechoslovakia, 3-5 September 1992 - Strejc, Vladimir (Published for the International Federation of Automatic Control by Pergamon Press, 1992)
Provides a useful reference source on system structure and control. Covers, linear systems, nonlinear systems, robust control, implicit system, chaotic systems, singular and time-varying systems.